Midlife vascular risk factors and Alzheimer's disease in later life: longitudinal, population based study - Kivipelto, Miia (BMJ, 2001)
OBJECTIVE: To examine the relation of midlife raised blood pressure and serum cholesterol concentrations to Alzheimer's disease in later life. DESIGN: Prospective, population based study. SETTING: Populations of Kuopio and Joensuu, eastern Finland. PARTICIPANTS: Participants were derived from random, population based samples previously studied in a survey carried out in 1972, 1977, 1982, or 1987. After an average of 21 years' follow up, a total of 1449 (73%) participants aged 65-79 took part in the re-examination in 1998. MAIN OUTCOME MEASURES: Midlife blood pressure and cholesterol concentrations and development of Alzheimer's disease in later life. RESULTS: People with raised systolic blood pressure (⩾160 mm Hg) or high serum cholesterol concentration (⩾6.5 mmol/l) in midlife had a significantly higher risk of Alzheimer's disease in later life, even after adjustment for age, body mass index, education, vascular events, smoking status, and alcohol consumption, than those with normal systolic blood pressure (odds ratio 2.3, 95% confidence interval 1.0 to 5.5) or serum cholesterol (odds ratio 2.1, 1.0 to 4.4). Participants with both of these risk factors in midlife had a significantly higher risk of developing Alzheimer's disease than those with either of the risk factors alone (odds ratio 3.5, 1.6 to 7.9). Diastolic blood pressure in midlife had no significant effect on the risk of Alzheimer's disease. CONCLUSION: Raised systolic blood pressure and high serum cholesterol concentration, and in particular the combination of these risks, in midlife increase the risk of Alzheimer's disease in later life.